(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Human beings depend on vision to obtain external information from their surroundings. It is, therefore, difficult for visually impaired people to perceive visual sensations in their daily lives. Currently, there are many related designs for the convenience of visually impaired people in urban construction and daily use. Still, little research has been done on their clothing design, especially designs that combine their functional and emotional requirements. In this study, interviews were conducted to examine the difficulties visually impaired people face in dressing and their functional and emotional requirements for clothing. Based on the design investigation of visually impaired people and the interview survey on their requirements for clothing, this study also explored the application of the sensory compensation design concept (mainly tactile compensation) in clothing design. As a result, four clothing styles were designed to meet their physical and psychological needs. It is hoped that the study will provide a way of thinking about clothing design for visually impaired people and call for more attention and help.